Assistance to forestry: what have we learnt? - Persson, R. (2000)
Assistance given to forestry, such as official development assistance in general, presents problems. It is well known that commitment and ownership are needed to achieve success. However, projects are still very much donor-driven. The best way to overcome current problems is to support developing countries' own strategies for development in general or in selected sector but such an approach is not very likely. Support for capacity building, research, learning, strengthening of analytical capacity and other 'basics' should then be favoured as a second 'best bet'. The main objective must be to strengthen domestic capacity within developing countries so that they can better appreciate the importance of forestry and take full charge of their own forestry development. Conditions imposed by donors or the pushing of donor agendas do not work in the long run.